2020
DOI: 10.1016/j.heliyon.2020.e04885
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of Irvingia gabonensis, Detarium microcapum, Mucuna pruriens and Brachystegia eurycoma seeds

Abstract: A culinary enhancer is a substance that enhances the flavor and other properties of soups, stews and foods. Normally in flour form, culinary enhancers are used to enhance the proximate composition, viscosity, flavor and some other rheological and functional properties of soups and convenience foods. Physical properties of culinary seeds are utilized in the development of their handling, storage and processing facilities. The unit operations in the process of converting culinary seeds into flour include handlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…The cultivars of pearl millet collected and maintained at four different equilibrium moisture content (MC) were subjected to different physical and mechanical tests. Mean values and their standard deviations of selected engineering properties measured at four different equilibrium moisture contents of 10%, 15%, 20%, 25% (wb) were presented in were also found for pearl millet (Nwabueze et al, 2020) (Jain & Bal, 1997) (Asoiro et al, 2020) (Koocheki et al, 2007). The GMD value for all varieties increased linearly as the moisture level increased (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The cultivars of pearl millet collected and maintained at four different equilibrium moisture content (MC) were subjected to different physical and mechanical tests. Mean values and their standard deviations of selected engineering properties measured at four different equilibrium moisture contents of 10%, 15%, 20%, 25% (wb) were presented in were also found for pearl millet (Nwabueze et al, 2020) (Jain & Bal, 1997) (Asoiro et al, 2020) (Koocheki et al, 2007). The GMD value for all varieties increased linearly as the moisture level increased (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…5 Nevertheless, there is greater utilization of the kernel, hence, it is a common practice to split the fruit into two using cutlass, in other to remove the split cotyledon (kernel) with knife, after which the flashy mesocarp is discarded, while the kernel is used for number of purposes. 9 Over the years, researches on I gabonensis kernel (IGK) majorly have been on its nutritional and medicinal applications, as well as the used of the milled kernels as condiment in soup as thickener, due to its rich fat and protein content. [10][11][12] Medicinally, it is used in body weight reduction of obese persons.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonally (between April to July), I gabonensis tree produces lots of edible fruits which are often not consumed, since the kernel component has greater value 5 . Nevertheless, there is greater utilization of the kernel, hence, it is a common practice to split the fruit into two using cutlass, in other to remove the split cotyledon (kernel) with knife, after which the flashy mesocarp is discarded, while the kernel is used for number of purposes 9 …”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the pulp of this fruit is eaten fresh and the seeds are used as a food additive, and as such possess superb economic and nutritional advantages [7]. They are good sources of phytochemicals including the likes of alkaloids, flavonoids, saponins, tannins, and glycosides, as well as proteins, minerals, vitamins, carbohydrates, fats, and soluble fibres [8]. Studies have shown that Irvingia gabonensis pulp extract possesses therapeutic potentials which are beneficial, including but not limited to weight loss [3] and antioxidant activity [9].…”
Section: Introductionmentioning
confidence: 99%